ANALISIS UJI ORGANOLEPTIK TAPAI SINGKONG PADA PRODUK COOKIES SEBAGAI UPAYA MENINGKATKAN EKSISTENSI TAPAI SINGKONG DI KOTA BANDUNG - Gusnadi, Dendi (Akrab Juara : Jurnal Ilmu-ilmu Sosial, 2019)
This research is discussing the use of Fermented Cassava as a sugar substitute ingredients in butter cookies. This research was conducted because of the interest of people to bring Fermented Cassava as a souvenir from west java is decreased. Fermented Cassava is an alternative of sugar subtitute for people who have diabetes. They can still be able to consume cookies without worrying about the sugar content in them. Fermented Cassava is also have a lot of nutrition that good for human body. The purpose of this research is to find a good formulation of butter cookies recipe using Fermented Cassava as a substitute for sugar with creaming method, and consumer acceptance test for butter cookies method. This research was conducted using the research and development method and consumer acceptance test was carried out by organoleptic testing to 500 consumers by distributing questionnaires.The result of the research showed that the recipe formulation suitable for fermented cassava based on butter cookies as a sugar substitute is 200 gram of margarine, 200 grams of butter, 400 grams of fermented cassava, 100 grams of powdered milk, 300 grams of low protein flour, 100 grams of almond powder, 100 grams cornstrach, 100 grams of raisin.The consumer acceptance test with a scale value of 4-5, by obtaining an average percentage is 63,4%. The Innovation of butter cookies based on fermented cassava as substitution for sugar obtained a number of nutritional results namely 48,46% carbohydrates, 8,82% fat and 26,98% sugar.